Pola Degradasi Fraksi Serat Serbuk Pelepah Sawit yang Diperkaya Mineral Zinc (Zn) Secara In Sacco - Anggriawan Naidilah Tetra Pratama; Gatot Muslim; Armina Fariani (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Pratama ANT, Gatot M. Fariani A. 2022. Fiber degradation patterns of oil palm frond enhanced mineral zinc (Zn) by In Sacco. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2020. pp. 839-846. Palembang: Penerbit & Pencetakan Universitas Sriwijaya (UNSRI).This study was aimed to determine the pattern of degradation fiber fractions (NDF, ADF, Hemicellulose, and Cellulose) in Oil Palm Frond by in Sacco method. This study was conducted from February to April 2021 at the Laboratory of Nutrition and Animal Feed Animal Husbandry Study Program, Faculty of Agriculture, Sriwijaya University. The Experimental design used was competely randomized design (CRD) with 3 treatments and 3 replication. The treatments were palm oil frond powder as control (P0), palm oil frond powder + 1% mineral Zinc (P1), and palm oil frond powder + 3% mineral zinc (P2). Parameters observed were degradation patterns which included total digestibility and kinetic degradation. Treatment differences were analyzed with SPSS software and Duncan's Test. The results of this study indicate the supplementation of mineral zinc 1-3% had not shown a significant different on the digestibility value.